Antepartum Haemorrhage: The Arguments and Its Implication to Muslim Parturient - Muhamad Rafiqi Bin Hehsan (USIM Press, 2024)
Pregnancy and bleeding throughout pregnancy are the two entities that cannot be separated. The implication of this issue leads to differences of thought, understanding and interpretation of the Islamic law, and affect the consequences of ibadah, worship to God. Although there are many resources that explores about this issue, but the understanding among parturient is seen inconclusive. Therefore, this article will discuss the condition of antepartum haemorrhage as well as the implications of it to Islamic law. This study uses a qualitative research methodology by analysing primary and secondary documents such as the classical books as well as academic writings in the journals. The findings of the study indicate that there are differences or argument regarding the implication to Islamic law and related with current issue. In addition, this article has also found that there are implications on the ibadah of parturient if the issues are not resolved due to differences of argument. Therefore, this article suggests for improvement in part of knowledge and understanding toward the issue of antepartum haemorrhage in order to ensure consistency in worship towards God.